Antibacterial Activity of Katang-Katang Leaf Extract Gel against Staphyloccus Aureus - Haryati, Eti; Sugiarto, Anto; Zuniarto, Ahmad Azrul; Hakkin, Atini Sabila (Newinera Publisher, 2025)
Infectious diseases are one of the health problems faced by developing countries such as Indonesia. Various methods are used to treat skin infections caused by Staphylococcus aureus bacteria, one of which is traditionally using plants, namely katang-katang leaves which have active compounds of flavonoids, alkaloids, saponins and tannins as antibacterials. This study aims to determine the antibacterial activity of the gel preparation of katang-katang leaf extract (Ipomea pes-caprae) to determine the concentration that has the greatest antibacterial activity and to determine the physical properties. Gel preparations were made with concentrations of 15%, 20%, and 25%. The test method was carried out using the in vitro disc diffusion method and physical properties tests were carried out which included organoleptic tests, homogeneity tests, pH tests, spreadability tests, adhesion tests and viscosity tests. Data analysis was carried out using normality tests, homogeneity tests, anova and post hoc test. The results of research testing the antibacterial activity of katang-katang leaf extract gel at a concentration of 15% was 3.27 mm, 20% was 4.97%, 25% was 5.97 mm, K+ was 10.97 mm and K- was 0 mm. Katang-katang leaf extract gel has antbacterial activity that is not equivalent to the positive control, katang-katang leaf extract gel does not meet the preparation evaluation requirements and is unstable during storage. From these results it can be concluded that the katang-katang leaf extract gel has antibacterial activity against Staphylococcus aureus and the katang-katang leaf extract gel does meet the preparation evaluation requirements and is unstable during storage.